Anak the movie (Quezon City Star Cinema, 2003)
Anak is the story of a mother's agony and her desperate attempt to piece back the broken fragments of her shattered family after years of working abroad under abusive conditions in order to provide a better life for her family.
DVD
Vilma Santos, Claudine Barreto, Joel Torre.
Keywords: Feature Films; Mother and child--Drama.